Konjac needs domestication - Misra, R. S. (Indian Horticulture, 2019)
The genus Amorphophallus, consisting of nearly 200 species worldwide, is distributed predominantly in tropical Asian and African countries. Only, A. paeoniifolious (Dennst.) Nicolson and A. konjac K. Koch, are commercially cultivated. Other species are wild, endemic or cultivated locally in small regions. A. paeoniifolius is basically cultivated as a food crop. Konjac (Amorphophallus konjac syn. A. rivieri) is native to warm subtropical to tropical eastern Asia (from Japan and China south to Indonesia). It is an important commercial crop grown in China, Japan, Indonesia, and elsewhere in subtropical Asia.